Advanced research of the impact of rotor bars anisotropic conductivity on starting torque of an induction motor with a die-cast copper cage - Chuvashev, V.A.; Varenyk, Ye.A.; Papazov, Yu.N.; Chuvankov, V.Yu.; Zheleznyakov, A.V.; Olenchenko, A.V.; Moukhametchine, N.A. (Електротехніка і електромеханіка, 2006)
Изложены результаты исследований влияния анизотропии проводимости стержней ротора на пусковой момент асинхронного двигателя, стендовых и эксплуатационных испытаний взрывозащищенного двигателя типа 2ЭКВ3,5-210 мощностью 210 кВт с литой анизотропной медной обмоткой ротора. Викладено результати досліджень впливу анізотропії провідності стрижнів ротора на пусковий момент асинхронного двигуна, стендових і експлуатаційних іспитів вибухозахищеного двигуна типу 2ЕКВ3,5-210 потужністю 210 квт із литою анізотропною мідною обмоткою ротора. The paper deals with an optimal design of an induction motor with a die-cast copper cage rotor characterized by an anisotropic layer in the upper part of the rotor bars. 1D FEM optimization of an explosion-proof induction motor with a die-cast copper rotor with overall parameters of a commercial induction motor with a die-cast aluminum rotor (180 kW, 1140 V, 1500 rpm) is made with the help of numeric computations. In the paper, the design features and experimental results are given. It is shown that induction motors with a special “starting” layer placed in the upper part the diecast copper rotor bar have maximum value of starting torque for relative conductivity factors ranging from 0.3 to 0.5. The basic performance data obtained in both bench and service tests of a prototype 210kW induction motor are in close agreement with analytical data.